No cardiac phase bias for threat-related distance perception under naturalistic conditions in immersive virtual reality - Felix Klotzsche; Paweł Motyka; Aleksander Molak; Václav Sahula; Barbora Darmová; Conor Byrnes; Iveta Fajnerová; Michael Gaebler (Royal Society Open Science)
Previous studies have found that threatening stimuli are more readily perceived and more intensely experienced when presented during cardiac systole compared with diastole. Also, threatening stimuli are judged as physically closer than neutral ones. In a pre-registered study, we tested these effects and their interaction using a naturalistic (interactive and three-dimensional) experimental design in immersive virtual reality: we briefly displayed threatening and non-threatening animals (four each) at varying distances (1.5–5.5 m) to a group of young, healthy participants (n = 41) while recording their electrocardiograms (ECGs). Participants then pointed to the location where they had seen the animal (approx. 29 000 trials in total). Our pre-registered analyses indicated that perceived distances to both threatening and non-threatening animals did not differ significantly between cardiac phases—with Bayesian analysis supporting the null hypothesis. There was also no evidence for an association between subjective fear and perceived proximity to threatening animals. These results contrast with previous findings that used verbal or declarative distance measures in less naturalistic experimental conditions. Furthermore, our findings suggest that the cardiac phase-related variation in threat processing may not generalize across different paradigms and may be less relevant in naturalistic scenarios than under more abstract experimental conditions.